Využití controllingu v podniku - Plecitá, Terezie (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Diplomová práce se zabývá analýzou a optimalizací controllingu ve vybraném podniku. Práce je rozdělena do tří hlavních částí. V první, teoretické části, jsou definovány základní pojmy controllingu. Ve druhé části je hodnocen stávající systém controllingu v podniku a jsou analyzovány odchylky dosažených výsledků v roce 2023 od finančního plánu. Poslední, návrhová část, obsahuje možná řešení pro zlepšení využití controllingu v podniku.

The diploma thesis focuses on the analysis and optimization of controlling in a selected company. The thesis is divided into three main parts. The first, theoretical part, defines the basic concepts of controlling. In the second part the existing controlling system in the company is evaluated and analyzes deviations of achieved results from the financial plan for the year 2023. The final, proposal part, presents a possible solution for improving the use of controlling in the company.
Application of Management Control System in a Business
Keywords: controlling; plánování; analýza odchylek; kontrola; reporting; controlling; planning; analysis of deviations; control; reporting